Gene expression of cultured human chondrocytes as a model for assessing neutralization efficacy of soluble TNFα by TNFα antagonists. Issue 3 (May 2015) - Barlič, Ariana; Žigon, Sara; Blejec, Andrej; Kregar Velikonja, Nevenka
Abstract Tumor necrosis factor-alpha (TNFα) antagonists are efficacious in the treatment of various immune-mediated inflammatory diseases. Because of rapidly growing demand for developing new or biosimilar versions of these biologicals, the need to create in vitro testing models that best represent physiological conditions is increasing. Primary human chondrocytes were used for potency evaluation and comparison between the molecular effects of anti-TNFα biologicals. Infliximab and etanercept were chosen to assess the suitability of chondrocyte cell culture for determination of anti-TNFα neutralization efficacy employing quantitative reverse transcription-polymerase chain reaction (qRT-PCR) technology. Use of both anti-TNFα biologics resulted in decrease of TNFα-stimulated expression of various matrix metalloproteinases, interleukins and other inflammation-related genes in our cell model. Significant differences in inhibition efficacy of etanercept and infliximab were observed, which were confirmed also on protein level. To evaluate the potency of anti-TNFα biologicals, a selection of TNFα-responsive target genes was made from the gene array data. The selected genes were employed in development of statistical model, which enables comparability of anti-TNFα biologicals. The presented analytical approach is suitable for assessment of the neutralization efficacy of various anti-TNFα biologicals. As such, it can be used for additional comprehensive characterization and comparability of TNF antagonists in preclinical drug testing.